Marketing Strategy for Welding Workshops in the New Normal Era after the Covid-19 Pandemic - Andika Isma; Andi Hidayatullah; Agung Winarno; Agus Hermawan (Pinisi Business Administration Review, 2020)
The Covid-19 pandemic has a major impact on all aspects and sectors of public life, especially business actors. The impact of the Covid-19 Pandemic was also experienced by welding workshops, one of which was the Barakka Las workshop. This study aims to determine the implementation of marketing strategies in the welding workshop business "Barakka Las" in the New Normal Era after the Covid-19 Pandemic through the creation and design of social media and websites. This research uses a qualitative approach with a case study research method. The data were obtained through collecting supporting theories and conducting in-depth interviews with the owner of the "Barakka Las" welding workshop. From the results obtained, in increasing brand loyalty and reaching wider consumers, Barakka Las implemented a digital marketing strategy through social media such as Instagram, Facebook, Twitter and Youtube and through websites with various interesting promotional content and additional information about the Covid-19 prevention protocol